2020
DOI: 10.1186/s12995-020-00282-z
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 aggravates inflammatory injury through TLR4 in chlorine gas-induced acute respiratory distress syndrome

Abstract: Background Chlorine gas (Cl2) exposure remains a public health concern in household, occupational, and transportation accidents around the world. The death rate associated with acute respiratory distress syndrome (ARDS) caused by high concentrations of Cl2 is very high, mainly because the pathogenesis of ARDS remains unclear. Histone H4 has been identified as an important endogenous pro-inflammatory molecule. The present study aimed to examine the pathogenic role of histone H4 in Cl2-induced AR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…animal models and patients of ARDS, extracellular histones have been proven to be associated with damages [35,36]. Study showed that heparin/low molecular weight heparin exerted a positive effect on mortality in COVID-19 patients by neutralizing the extracellular histones [37].…”
Section: Discussionmentioning
confidence: 99%
“…animal models and patients of ARDS, extracellular histones have been proven to be associated with damages [35,36]. Study showed that heparin/low molecular weight heparin exerted a positive effect on mortality in COVID-19 patients by neutralizing the extracellular histones [37].…”
Section: Discussionmentioning
confidence: 99%
“…LPS stimulation leads to systemic inflammatory and toxic responses by activating Toll-like receptors ( 21), the complement system (22), and inflammasome pathways, which provoke apoptosis, necrosis, and NET formation (7), and histone release into the circulation. These extracellular histones play a pathogenic role in the development of ARDS through promoting alveolar macrophage proptosis (23), direct cytotoxic endothelial damage (24) and pro-inflammatory effects with cytokine production (25) (26), resulting in overwhelming cell damage and death (22). Furthermore, these extracellular histones can induce platelet aggregation (28) and coagulation activation (29), immuno-thrombosis formation (30) and innate immunity by activating Toll-like receptors and the NLRP3 inflammasome (27).…”
Section: Discussionmentioning
confidence: 99%
“…Histone H4 is one of the five core histone proteins that are involved in the formation of nucleosomes in chromatin [ 81 ]. The unexpected cytotoxic role of extracellular H4 is reported in sepsis via the interaction with toll-like receptor (TLR) 2 and 4, which are upregulated in inflammatory injuries [ 82 ]. Regarding Hsp90ab1 (aka Hsp90b), it is shown in osteosarcoma cells that secreted Hsp90ab1 proteins inhibit the activation of latent TGFβ [ 83 ].…”
Section: Double-edged Role Of Tumor-suppressing Proteinsmentioning
confidence: 99%